2020
DOI: 10.3389/fmicb.2020.01815
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Carbon Fixation in a Salamander-Alga Symbiosis

Abstract: The unique symbiosis between a vertebrate salamander, Ambystoma maculatum, and unicellular green alga, Oophila amblystomatis, involves multiple modes of interaction. These include an ectosymbiotic interaction where the alga colonizes the egg capsule, and an intracellular interaction where the alga enters tissues and cells of the salamander. One common interaction in mutualist photosymbioses is the transfer of photosynthate from the algal symbiont to the host animal. In the A. maculatum-O. amblystomatis interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Until now, the majority of documented natural endosymbiotic relationships have been observed in invertebrates. [ 29 ] However, establishing long‐term symbiotic relationships between microorganisms and mammalian cells has proven challenging due to the high degree of evolution and exclusivity characterizing mammalian cells. While mammalian macrophages are capable of spontaneously phagocytosing cyanobacteria, it has been demonstrated that they are ill‐suited to function as host cells for endosymbiosis with cyanobacteria, primarily due to their robust immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the majority of documented natural endosymbiotic relationships have been observed in invertebrates. [ 29 ] However, establishing long‐term symbiotic relationships between microorganisms and mammalian cells has proven challenging due to the high degree of evolution and exclusivity characterizing mammalian cells. While mammalian macrophages are capable of spontaneously phagocytosing cyanobacteria, it has been demonstrated that they are ill‐suited to function as host cells for endosymbiosis with cyanobacteria, primarily due to their robust immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, injection of these green algae into zebrafish eggs formed chimeras that remained viable for several days and after subsequent extraction from the larvae, the algae continued to grow (Alvarez et al, 2015). This suggests that the period of amalgamation with an animal had no obvious detrimental impact on the fertility of these phototrophic microorganisms in line with natural symbiotic interactions between algae and vertebrates (Burns et al, 2020;Kerney et al, 2011). Moreover, the employment of Xenopus tadpoles at mid-larval stages for experiments such as presented here might be advantageous for further exploring the beneficial range of systemically introduced phototrophic microorganisms on brain metabolism and electrical activity because the innate immune system in these animals is only completed after metamorphosis (Godwin and Rosenthal, 2014).…”
Section: Systemic Reaction Of the Immune System Upon Injectionmentioning
confidence: 94%
“…Provided photosynthetic microorganisms such as algae and cyanobacteria can be inserted and distributed throughout the tissue such as the brain, their O 2 -producing ability might directly supplement the respective needs of animals. In fact, natural symbiotic interactions between such microorganisms and animals are reported for members of the phyla Porifera (sponges), Cnidaria (corals, sea anemones; Venn et al., 2008 ) and also salamander species ( Burns et al., 2020 ; Kerney et al., 2011 ). By mimicking this natural principle, microalgae have occasionally been employed in biomedical science as efficient O 2 source, mostly to supplant absent blood perfusion of isolated tissue ( Chávez et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oophila within the capsular chamber provide an increase in the partial pressure of oxygen during the day, potentially remove nitrogenous waste, and have been reported to transfer photosynthate to the amphibian embryos (Bachmann et al 1986 ; Goff and Stein 1978 ; Graham et al 2013 ; Kerney 2011 ; Pinder and Friet 1994 ), which may lead to acceleration of embryonal development, larger sized embryos, increased viability and hatching success (Gilbert 1942 , 1944 ). However, other studies have reported no measurable exchange of photosynthate from algae to amphibian embryos (Burns et al 2020 ). Additional effects by the algae, such as a reduction of micro-organisms that are potentially harmful to the host, have been hypothesized (Kim et al 2014 ) but not yet tested.…”
Section: Introductionmentioning
confidence: 92%
“…gracile (Kerney et al 2019 ; Marco and Blaustein 2000 ) egg capsule chambers. These O. amblystomatis isolates have been used in studies of gene expression (Burns et al 2017 ; Kerney et al 2019 ), carbon fixation (Burns et al 2020 ), and host-symbiont fidelity (Kerney et al 2019 ). As an exception, a few isolates from A .…”
Section: Introductionmentioning
confidence: 99%